(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to know the pressures of e-learning as perceived by the faculty members at Al-Mustansiriya University. The research sample consisted of (58) faculty members at Al-Mustansiriya University, on whom a scale of (30) items was applied that measured e-learning pressures, and the scale was divided into three aspects: Administrative and material aspects (9) paragraphs And aspects related to the teacher and the student (13) paragraphs; And aspects related to e-learning (8) paragraphs. The results of the research showed that the male professors suffer from the lack of applications in the Arabic language more than the female professors, and this creates pressure on the university professor and negatively affects him, but they have a high ability to face the difficult conditions that may face them of whatever kind and overcome these difficulties in front of their students to raise their scientific level . The results of the research also showed that professors with scientific specializations suffer at a moderate level from students ’lack of response to this method of education (e-learning). Professors with humanitarian specializations suffer greatly from the lack of applications in the Arabic language, as the method of e-learning is a modern scientific method that requires prior preparation before its application. In light of the results, some recommendations were reached